Revitalizing Philippine irrigation A systems and governance assessment for the 21st century - Briones, Roehlano M. (Quezon City Philippine Institute for Development Studies, 2021)
After years of relative neglect, irrigation has again emerged as the single largest budgetary outlay in government-funded agricultural programs after the world rice price crisis of 2008. Since then, priority for irrigation and rice agriculture has been sustained over three administrations. Never has the goal of closing the gap between actual and potential irrigable area been nearer than today.

This volume has evaluated the resurgent irrigation development program to date, covering national systems, communal systems, and various program considerations, such as water resource assessment, governance issues, recent policy shifts (e.g., Free Irrigation Service Act), and benefit-cost comparison. The analysis will hopefully serve as input to the continued implementation of the irrigation development program, which, as argued earlier, has yet a long way to go. The assessment has sought to combine both field-based qualitative and ocular assessment, with state-of-the-art quantitative assessment (including hydraulic and economic modeling). Based on this assessment, the authors offer a set of practical and hopefully useful recommendations, primarily for the National Irrigation Administration, as well as for the broad set of stakeholders in the national irrigation development agenda.

This volume won the 2022 Outstanding Book Award from the National Academy of Science and Technology.
Chapter 1 : Irrigation and agricultural development -- Chapter 2 : National irrigation systems -- Chapter 3 : Communal irrigation systems -- Chapter 4 : Water resources component -- Chapter 5 : Irrigation water governance -- Chapter 6 : An assessment of the Free Irrigation Act -- Chapter 7 : Benefit - cost analysis of the resurgent irrigation system program of the Philippines -- Chapter 8 : Assessing the resurgent irrigation development program of the Philippines : synthesis report -- References -- The authors
Includes bibliographical references
Keywords: Irrigation -- Philippines; Water resources development -- Philippines